A Comparison of Shura and Deliberative Democracy Decision-Making Methods: Similarities and Differences - Seyfeddin Neslinebi (Research Synergy Foundation, 2024)
Shura is a decision-making model in Islamic governance that aims to make the right decisions for society in general and inclusively. While Allah has established the general framework for various issues, particularly administrative matters, the specific details are left to human discretion, to be determined through Shura and consultation. The significance of Shura is underscored in verse 38 of Surah Ash-Shura, where it is mentioned alongside fundamental Islamic principles such as prayer and zakat. Conversely, the democratic management model, a human construct, has evolved since ancient Greece, undergoing transformations resulting in diverse forms such as direct, representative, liberal, social, radical, dialogic, agonistic, and deliberative democracy. This study aims to compare the principles of Islamic governance with those of deliberative democracy. By analyzing their similarities and differences, this research seeks to evaluate the compatibility of these two governance frameworks. The findings provide insights into their potential alignment or divergence, contributing to a broader understanding of decision-making practices in diverse cultural and philosophical contexts.